Retroperitoneal Robot-Assisted Laparoscopic Partial Nephrectomy for Horseshoe Kidney: A Case Report - Zhang, Dongxu; Lu, Youyi; Sun, Fengze; Yao, Huibao; Wu, Jitao; Wang, Jipeng (Frontiers in Urology, 2021)
Abstract Background: Horseshoe kidney (HSK) has always been a challenge for urologists depending on its particular anatomy. We report a case of renal tumor in a patient with HSK, who underwent tumor resection by retroperitoneal robot-assisted laparoscopic partial nephrectomy. Case Presentations: A 47-year-old man with HSK presented to our hospital with a solid renal mass. Computed tomography urography (CTU) showed a 4.3 × 4.4 cm mass in the upper pole of the right kidney. Patients received a retroperitoneal robot-assisted laparoscopic partial nephrectomy on basis of CT three-dimensional (3D) reconstructions. Conclusion: The present case report highlights the feasibility of retroperitoneal robot-assisted laparoscopic partial nephrectomy for horseshoe kidney, and the advantages of preoperative CT scan with three-dimensional reconstructions.